Downstream Impacts of Water Pollution in the Upper Citarum River, West Java, Indonesia : Economic Assessment of Interventions to Improve Water Quality - Asian Development Bank (Asian Development Bank, Manila and World Bank, Washington, DC, 2014)
The Economics of Sanitation Initiative (ESI) of the World Bank's Water and Sanitation Program (WSP) commenced in East Asia and the Pacific region in 2006 to generate and disseminate economic evidence on sanitation. A phase one study in five countries of the region, including Indonesia, assessed the economic costs of inadequate sanitation to raise the profile of sanitation nationally. A phase two study compared the costs with the benefits of a range of sanitation intervention options in five physical locations in Indonesia, to assist decision makers in their choice of sanitation technology and delivery method. Since the demonstrated successes of ESI in the East Asia and Pacific region, ESI has become a global flagship program of WSP. However, some economic benefits have not been fully evaluated in monetary terms because of methodological difficulties in valuing nonmarket impacts, the paucity of underlying data sets, and the difficulties inherent in attributing observed impacts to poor sanitation. Among these hard-to-measure benefits are the impacts of poor sanitation on water resources. Hence, the purpose of this study was to develop and pilot test a specific methodology for valuing a wider range of impacts related to water resource pollution in Indonesia.